How to design a flower garden - Ball, Jeff; Barr Entertainment (Irwindale, CA Barr Entertainment, 1991)
Selection of sites, and choice of flowers for easy-maintenance gardens, as well as irrigation, mulching, and compost for full-season bloom
Endorsed by the National Gardening Association
DVD
1
Keywords: Flower gardening; Flowers; Gardening; DVD-Video discs -- 1986